2021
DOI: 10.1177/09544054211014846
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and optimization on field shaper structure parameters in magnetic pulse welding

Abstract: Magnetic pulse welding is a high-speed welding technology, which is suitable for welding light metal materials. In the magnetic pulse welding system, the field shaper can increase the service life of the coil and contribute to concentrating the magnetic field in the welding area. Therefore, optimizing the structure of the field shaper can effectively improve the efficiency of the system. This paper analyzed the influence of cross-sectional shape and inner angle of the field shaper on the ability of concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The rejection of steel FSs in favor of copper, bronze, or aluminum FSs is a forced measure and is caused by the low field homogeneity of steel inductor systems. However, solid FSs of copper or beryllium bronze fail rather quickly when welding steel parts due to FS geometry changes or crack development during the first few magnetic field pulses [7,10,31]. In our case, after 10 pulses of a 40-50 T magnetic field, the was no significant evidence of surface destruction or plastic deformation.…”
Section: Mpw Experimentsmentioning
confidence: 51%
See 1 more Smart Citation
“…The rejection of steel FSs in favor of copper, bronze, or aluminum FSs is a forced measure and is caused by the low field homogeneity of steel inductor systems. However, solid FSs of copper or beryllium bronze fail rather quickly when welding steel parts due to FS geometry changes or crack development during the first few magnetic field pulses [7,10,31]. In our case, after 10 pulses of a 40-50 T magnetic field, the was no significant evidence of surface destruction or plastic deformation.…”
Section: Mpw Experimentsmentioning
confidence: 51%
“…A similar study of plane geometry was carried out in the work of Zhang [30]. Chen and colleagues [31] analyzed the different cross-sectional shapes and inner surface angles of FSs and suggested the use of a rounded shape as an intermediate between stepped and tapered shapes. The results of numerical simulations and experiments have shown that changing the shape from conventional and tapered (similar to Figure 3b) to concave (Figure 3c) could increase the magnetic field flux by ∼10% with virtually no loss in strength.…”
Section: The Basics Of the Mpw Process And The Role Of The Field-shapermentioning
confidence: 89%
“…A similar study for plane geometry was carried out in the work of Zhang [30]. Chen and colleagues [31] analyzed the different cross-sectional shape and inner surface angle of the FS and suggested the use of a rounded shape as intermediate between stepped and tapered. The results of numerical simulations and experiments have shown that changing the shape from conventional tapered (similar to Figure 3b) to concave (Figure 3c) can increase the magnetic field flux by ∼10%, with virtually no loss in strength.…”
Section: Basics Of Mpw Process and The Role Of Field-shapermentioning
confidence: 86%